2021
DOI: 10.1007/s00167-021-06621-9
|View full text |Cite
|
Sign up to set email alerts
|

Good clinical outcomes and return to sports after hybrid closed-wedge high tibial osteotomy

Abstract: Purpose This study aimed to investigate preoperative sports participation and postoperative clinical outcomes including a return to sports (RTS) after hybrid closed-wedge high tibial osteotomy (CWHTO) for medial compartment osteoarthritis of the knee. Characteristic of Hybrid CWHTO was deined as extra-articular lateral closed and medial open wedge osteotomy. Methods The patients who underwent hybrid CWHTO from January 2016 to December 2018 were retrospectively reviewed and divided them into sports and non-spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…There was no correction loss with or without delayed bone, and there was no signi cant difference in the clinical outcomes at 1 year postoperatively. In a previous study, the mean JOA score at 1 year postoperatively was 89 [14], which is similar to that in the present study. The data from the present study suggest that, even in the absence of bone union at 3 months postoperatively, good results can be achieved at 1 year postoperatively with appropriate weight-bearing management.…”
Section: Discussionsupporting
confidence: 92%
“…There was no correction loss with or without delayed bone, and there was no signi cant difference in the clinical outcomes at 1 year postoperatively. In a previous study, the mean JOA score at 1 year postoperatively was 89 [14], which is similar to that in the present study. The data from the present study suggest that, even in the absence of bone union at 3 months postoperatively, good results can be achieved at 1 year postoperatively with appropriate weight-bearing management.…”
Section: Discussionsupporting
confidence: 92%
“…Our GE group participants’ characteristics were age (66.9 ± 8.3 years), KL grade (severe OA rate: 75%), complication rate (bone resorption: 8.0%, Delayed union 3.8%), JOA score (preoperatively: 71.2 ± 11.9 to post 12 months: 91.4 ± 6.1), VAS (preoperatively: 29.4 ± 20.4 to post 12 months 1.2 ± 3.3). Previous study 3 , 5 , 15 – 17 ) , reported that age (56.7–69.2 years), KL grade (severe OA rate: 52–100%), and JOA score (preoperatively: 61.0–72.2 to post 12 months: 86.4–92.0), VAS (preoperatively: 46.0 ± 19.0 to post 12 months: 10.0 ± 0.9), complication (Delayed union 4.0%–8.5%). Compared to these previous studies, the present study resulted in less pain, fewer post-operative complications, and higher JOA scores.…”
Section: Discussionmentioning
confidence: 99%
“…HCWHTO is also identified for patellofemoral joint OA, strong varus deformity, and knee flexion contracture 2 ) . Although arthroplasty was prevalently the treatment of choice for severe knee OA, HCWHTO is increasingly being chosen when recreational and sports activities are desired 3 ) . The stable contact surface of the lateral tibial osteotomy side enables full loading at 2–3 weeks postoperatively, and the expeditious time to the bony union has the advantage of influencing a swift return to sports 3 , 4 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation